PEMANFAATAN SISTEM INFORMASI GEOGRAFIS UNTUK MENENTUKAN LOKASI POTENSIAL PENGEMBANGAN KAWASAN INDUSTRI DI KABUPATEN PATI - Agus Purwanto; I Iswandi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Pati is one of the regency in Central Java Province which has a strategic position because it is crossed by the Java pantura line and also directly borders the Java Sea which is a trade route in Indonesia. In the case of the construction of an industrial area the use of spatial data and analysis of Geographic Information Systems (GIS) can be used to determine potential locations suitable for the construction of industrial estates without overriding the environment and society. The results of the analysis of eight parameters are slope slope (29.54%), land distance to the main road (29.36%), land distance to infrastructure and trade center (8.25%), land use (8.21%), soil type (7.22%), land distance to rivers (5.23%), land distance to energy networks (6.75%), and land distance to communication networks (5.44%). The weighted overlay analysis of the scoring values of each parameter produces a location that is very suitable for industrial estates (S1) covering an area of 1221, 431 ha, suitable for industrial estates (S2) covering an area of 83749,160 ha, quite suitable (S3) covering 55024,181 ha, not suitable (N1) covering an area of 9169,273 ha, and not suitable (N2) covering an area of 388,637 ha whereas based on the intersect map analysis of the results of overlays and maps of the Pati Regency RTRW, the most suitable location for the industrial area is 24,220 ha. From the calculation, the potential location that can be used for industrial estates in Pati Regency is 1197,211 ha. This location is in Margorejo district, Pati district, Juwana district, Batangan district, Sukolilo district, and Tambakromo district.